Using emotion as information in future-oriented cognition: Individual differences in the context of state negative affect. (June 2016) - Marroquín, Brett; Boyle, Chloe C.; Nolen-Hoeksema, Susan; Stanton, Annette L.
Abstract: Predictions about the future are susceptible to mood-congruent influences of emotional state. However, recent work suggests individuals also differ in the degree to which they incorporate emotion into cognition. This study examined the role of such individual differences in the context of state negative emotion. We examined whether trait tendencies to use negative or positive emotion as information affect individuals' predictions of what will happen in the future ( likelihood estimation ) and how events will feel ( affective forecasting ), and whether trait influences depend on emotional state. Participants ( N  = 119) reported on tendencies to use emotion as information ("following feelings"), underwent an emotion induction (negative versus neutral), and made likelihood estimates and affective forecasts for future events. Views of the future were predicted by both emotional state and individual differences in following feelings. Whereas following negative feelings affected most future-oriented cognition across emotional states, following positive feelings specifically buffered individuals' views of the future in the negative emotion condition, and specifically for positive future events, a category of future-event prediction especially important in psychological health. Individual differences may confer predisposition toward optimistic or pessimistic expectations of the future in the context of acute negative emotion, with implications for adaptive and maladaptive functioning. Highlights: Future-event predictions are influenced by mood and use of affect as information. Study compared effects of state mood and individual differences in use of affect State and trait factors affected likelihood estimation and affective forecasting. Trait "following" positive feelings linked with optimism despite negative mood. Individual differences may determine adaptive/maladaptive cognition under distress.